Consumer-Based Product Creativity, Product-Brand Fit, and Product-Category Fit: Which is More Influential in Consumer Responses? - Shim, Soo In; Goh, Yi Sheng * (Universiti Sains Malaysia, 2022)
This study examines the effects of consumer-based product creativity (i.e., novelty and meaningfulness dimensions), product-brand fit, and product-category fit on attitude toward the product and purchase intention. A total of 544 university students participated in a survey, in which respondents were exposed to a stimulus product image and then required to respond to a questionnaire. Structural equation modelling results show that novelty and meaningfulness and product-brand fit significantly influence attitude, subsequently increasing purchase intention. Notably, meaningfulness, rather than product-brand fit, is found to be more influential on both the attitude and purchase intention. The importance of meaningfulness can be even more highlighted for the products less fitted for their category. Theoretical and practical implications are further discussed.